A Reusability Assessment of UCP-Based Effort Estimation Framework using Object-Oriented Approach - Che Ani, Zhamri; Basri, Shuib; Sarlan, Aliza (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Software effort estimation has become one of the most important concerns of software industries and Use Case Points (UCP) is seen as one of the most popular estimation models for object-oriented software development. Since year 2005, more than 10 UCP-based effort estimation techniques have been proposed either to give more options or to enhance the capability of UCP. However, there is no guidance for software practitioners to develop a quality UCP-based effort estimation applications. Therefore, we have proposed a new design framework for UCP-based technique to promote reusability in developing software applications. This paper will experiment and provide evidence showing that the framework achieved a good quality design using Quality Model for Objectoriented Design (QMOOD). The results showed that the framework has met five quality attributes and good to be reused as a guideline at the early stages of software development.